Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error - Tedja, Milly S.; Wojciechowski, Robert; Hysi, Pirro G.; Eriksson, Nicholas; Furlotte, Nicholas A.; Verhoeven, Virginie J. M.; Iglesias, Adriana I.; Meester-Smoor, Magda A.; Tompson, Stuart W.; Fan, Qiao; Khawaja, Anthony P.; Cheng, Ching-Yu; et al. (Nature genetics, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers. Transancestral GWAS meta-analysis in 160,420 individuals identifies 139 loci associated with refractive error, including myopia. Newly identified genes implicate pathways involved in eye growth and light signaling cascades.